2006
DOI: 10.1158/0008-5472.can-05-1237
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Tumorigenesis following Transgenic Expression of a Dominant Negative CHK2 Mutant

Abstract: A truncating allele of the cell cycle checkpoint kinase CHK2 is present in 1% of the population, conferring a moderate increase in breast cancer risk, and inactivation of chk2 enhances mammary tumorigenesis in mice with targeted inactivation of brca1. We used the mouse mammary tumor virus (MMTV) promoter to target expression of a kinase-dead CHK2 allele (D347A). Mammary tumors, of predominantly micropapillary histology, developed in 40% of MMTV-CHK2-D347A transgenic mice with an average latency of 20 months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The importance of the Chk2 kinase in cellular homeostasis is emphasized by the established link to its role as a tumor suppressor where certain and a very specific class of mutations lead to predisposition for various cancers (50). Chk2 null mice do not develop spontaneous tumors without additional genotoxic treatment, but the mice expressing the kinase-deficient version of Chk2 in mammary glands do develop mammary tumors spontaneously (51). The knock-in mouse with the human cancer predisposing Chk2*1100delC allele develops tumors with high frequency even without additionally induced genotoxic stress (52).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the Chk2 kinase in cellular homeostasis is emphasized by the established link to its role as a tumor suppressor where certain and a very specific class of mutations lead to predisposition for various cancers (50). Chk2 null mice do not develop spontaneous tumors without additional genotoxic treatment, but the mice expressing the kinase-deficient version of Chk2 in mammary glands do develop mammary tumors spontaneously (51). The knock-in mouse with the human cancer predisposing Chk2*1100delC allele develops tumors with high frequency even without additionally induced genotoxic stress (52).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations indicated that FVB females with prolactinomas and prolactin overstimulation of the mammary gland typically produce mammary adenosquamous carcinomas. 9,19,23 If true in all cohorts, prolactinrelated tumors could be readily identified and animals segregated. Importantly, these findings were not confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of 7,12-dimethylbenz[a]anthracene (DMBA), however, accelerates the formation of skin tumors (29). In contrast, mice transgenic for a kinase-dead, dominant-negative Chk2 under control of a mouse mammary tumor virus (MMTV) promoter developed mammary tumors but only after a latency period of Ϸ20 months (30).…”
mentioning
confidence: 99%